Pengembangan Kewirausahaan Berbasis Industri Kreatif Bagi Jamaah Wanita Majelis Taklim Di Desa Kepek - Umi Musaropah; Suharto Suharto; Daluti Delimanugari; Agus Suprianto; Rubini Rubini; Retno Kurnianingsih; Citra Ayudiati (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2019)
Entrepreneurship development based on creative industries for women congregation majelis taklim (MT) in Kepek village is carried out using the PAR (Participation Action Research) method which aims to encourage creative minds by pressing questions and participant-oriented guidance. Entrepreneurship development for MT female congregation in Kepek Gunung Kidul village can be achieved well. Among others are; There needs to be a follow-up in a series of mentoring and skills improvement, both for the main and supporting the business. The potential for good local wisdom can be converted into economic values. Massive development of marketing networks needs to be considered in order to have a bigger economic impact on the surrounding community. The government is advised to support deeper exploration of the local economic wisdom of the people of Gunung Kidul so that it can have a direct positive impact on its residents.